2020
DOI: 10.1158/0008-5472.can-18-4099
|View full text |Cite
|
Sign up to set email alerts
|

BACH1 Promotes Pancreatic Cancer Metastasis by Repressing Epithelial Genes and Enhancing Epithelial–Mesenchymal Transition

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is among the cancers with the poorest prognoses due to its highly malignant features. BTB and CNC homology 1 (BACH1) has been implicated in RAS-driven tumor formation. We focused on the role of BACH1 in PDAC, more than 90% of which have KRAS mutation. Knockdown of BACH1 in PDAC cell lines reduced cell migration and invasion, in part, by increasing E-cadherin expression, whereas its overexpression showed opposite effects. BACH1 directly repressed the expression of FOXA1 t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 48 publications
8
97
0
Order By: Relevance
“…Restoration of E-cadherin expression reverses these processes indicating a direct role for this adhesion molecule in PDA peritoneal dissemination [ 148 ]. BACH1 promotes PDA peritoneal metastasis by repressing E-cadherin and enhancing EMT, particularly in cases driven by KRAS mutation [ 81 ]. ARL4C is significantly expressed in PDA and promotes growth and metastasis of this disease [ 83 ].…”
Section: Molecular Mediators Of Cell Detachment From the Primary Tumomentioning
confidence: 99%
See 1 more Smart Citation
“…Restoration of E-cadherin expression reverses these processes indicating a direct role for this adhesion molecule in PDA peritoneal dissemination [ 148 ]. BACH1 promotes PDA peritoneal metastasis by repressing E-cadherin and enhancing EMT, particularly in cases driven by KRAS mutation [ 81 ]. ARL4C is significantly expressed in PDA and promotes growth and metastasis of this disease [ 83 ].…”
Section: Molecular Mediators Of Cell Detachment From the Primary Tumomentioning
confidence: 99%
“…In PDA, similar to ovarian and gastric cancers, loss of E-cadherin expression increases cell invasion in vitro and peritoneal dissemination in vivo , while restoration of E-cadherin expression reverses these processes [ 148 ]. As is ovarian cancer, BACH1 promotes PDA cell migration and invasion in part by repressing E-cadherin expression [ 81 ]. MSLN and MUC16 co-overexpression and mutual binding of MSLN to MUC16 markedly enhances PDA cell migration and invasion.…”
Section: Cell Invasion To the Underlying Connective Tissuementioning
confidence: 99%
“…In addition, chromVAR analysis showed that the most variable TF motifs across all the cells represented EMT regulators Smarcc1, Bach1 and c-Fos (Figure 4F and G). BACH1 has been reported to promote EMT by repressing the expression of a set of epithelial genes [46]. SMARCC1 interacts with NKX6.1 to activate EMT in HeLa cells[47].…”
Section: Resultsmentioning
confidence: 99%
“…Growth factor signal transduction pathway mediated by mTOR complex 1 (mTORC1) promotes cancer metabolism through key enzymes that regulate metabolic pathways. Inhibition of mTOR C1 reduces glycolysis of cancer cells [38,39].EMT can promote tumor cell infiltration and tumor metastasis and may also make tumor cells escape apoptosis induced by some factors [40,41]. This process also plays a key role in regulating cellular plasticity in normal human tissues and tumor tissues.…”
Section: Discussionmentioning
confidence: 99%